2009
DOI: 10.1101/gad.1857410
|View full text |Cite
|
Sign up to set email alerts
|

A histone chaperone, DEK, transcriptionally coactivates a nuclear receptor

Abstract: Chromatin reorganization is essential for transcriptional control by sequence-specific transcription factors. However, the molecular link between transcriptional control and chromatin reconfiguration remains unclear. By colocalization of the nuclear ecdysone receptor (EcR) on the ecdysone-induced puff in the salivary gland, Drosophila DEK (dDEK) was genetically identified as a coactivator of EcR in both insect cells and intact flies. Biochemical purification and characterization of the complexes containing fly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 55 publications
3
146
0
Order By: Relevance
“…However, molecular studies of DEK oncogenicity have mostly focused on roles of DEK in interphase cells, where DEK is constitutively bound to chromatin, and functions in transcription, replication and DNA repair. 18,31,36,[53][54][55][56][57] In this study we investigated the regulation of DEK in mitosis and found that endogenous DEK is removed from chromatin in early prophase and re-associates with chromatin in telophase as outlined in Figure 8A. Importantly, DEK over-expression leads to its aberrant retention on chromatin throughout mitosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, molecular studies of DEK oncogenicity have mostly focused on roles of DEK in interphase cells, where DEK is constitutively bound to chromatin, and functions in transcription, replication and DNA repair. 18,31,36,[53][54][55][56][57] In this study we investigated the regulation of DEK in mitosis and found that endogenous DEK is removed from chromatin in early prophase and re-associates with chromatin in telophase as outlined in Figure 8A. Importantly, DEK over-expression leads to its aberrant retention on chromatin throughout mitosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…DEK is a unique, non-histone, chromatin-associated protein that is evolutionarily conserved in higher eukaryotes, and represents the only member of its family. DEK can non-enzymatically bend DNA to introduce positive supercoils 17 and functions as a histone 3.3 chaperone both in Drosophila 18 and human cells. 19 It also is involved in the maintenance of heterochromatin by directly interacting with HP1a to enhance its binding to H3K9Me3.…”
Section: Introductionmentioning
confidence: 99%
“…125 Another report identified histone chaperone activities for DEK that strictly depended on its interaction with and phosphorylation by CK2, which resulted in gene activation. 126 As previously mentioned, in cell-free assays DEK could introduce constrained positive supercoils into DNA and facilitate the ligation of linear DNA molecules in vitro. 95,97 Most studies indicate that DEK binding to nucleic acids is not sequence-specific but rather has a preference for super-coiled and cruciform structures.…”
Section: Dek Regulates Chromatin Structure and Function In Normal Andmentioning
confidence: 99%
“…Whether this chromatin-remodeling factor is required for other HIRA complex-mediated H3.3 depositions is an open issue. Another protein, the chromatin-bound oncogene product DEK is suggested to be an H3.3 histone chaperone in Drosophila and human cells, with potential functions to direct its deposition at regulatory elements and enhance transcription [74]. Given that DEK also associates with DAXX [75], it is possible that DEK and DAXX act together in H3.3 deposition at regulatory elements.…”
Section: Additional Playersmentioning
confidence: 99%